1930
DOI: 10.1042/bj0240262
|View full text |Cite
|
Sign up to set email alerts
|

The decarboxylation of pectin

Abstract: EARLY work on the occurrence of pectins and hemicelluloses showed that these substances were normally to be found in association in the cell-wall, the relative amount of each being dependent on the condition of the tissue, i.e. whether lignified or non-lignified [Clayson, Norris, and Schryver, 1921]. Subsequent work [Candlin and Schryver, 1928] indicated the existence of an intimate relation between the two classes of substances, since pectin was shown to undergo decarboxylation under the influence of alkali, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1938
1938
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As these phenotypic assays on Vero cells are time-consuming and difficult to carry out on a large number of E. coli isolates the DNA colony hybridization genotypic assay using gene probes for EDP, SLTI and SLTII was performed with VTEC and non VTEC porcine isolates. The results of this work show that (i) EDP and SLTII probes cross-hybridized (ii) both EDP and SLTII probes hybridized to all VTEC but to none of the non VTEC isolates (iii) all E. coli isolates were negative using the gene probe for SLTI which does not seem to be common among porcine E. coli [6,7,20]. The genes encoding EDP show extensive homology with those encoding SLTII, but not with those encoding SLTI [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As these phenotypic assays on Vero cells are time-consuming and difficult to carry out on a large number of E. coli isolates the DNA colony hybridization genotypic assay using gene probes for EDP, SLTI and SLTII was performed with VTEC and non VTEC porcine isolates. The results of this work show that (i) EDP and SLTII probes cross-hybridized (ii) both EDP and SLTII probes hybridized to all VTEC but to none of the non VTEC isolates (iii) all E. coli isolates were negative using the gene probe for SLTI which does not seem to be common among porcine E. coli [6,7,20]. The genes encoding EDP show extensive homology with those encoding SLTII, but not with those encoding SLTI [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Some VTEC isolates associated with ED also produce one or more classical enterotoxins (Ent VTEC isolates) [4,[6][7][8]. The Ent VTEC isolates belonging to the O141 : K85 serotype usually produce STb alone ( [6], see also RESULTS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holt ( 5 ) and Linggood (10) have found that diphtheria toxin can be converted into toxoid a t 300 C. without the loss of 15-30 per cent of the flocculating activity which usually occurs at 37-41O C . In preparatory work with this less harshly treated crude material, the latter was found to be decidedly better.…”
Section: Purification Of Toxoid From Casein Hydrolysate Media Prodmentioning
confidence: 99%